Peningkatan Kualitas dan Kuantitas Kerajinan Rotan Menuju Trangsan Desa Wisata dalam rangka Meningkatkan Ekspor - Sri Suranta; Santoso Tri Hananto; Christiyaningsih Budiwati; M. Syafiqurrahman (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2019)
The purpose of implementing community service is the Export Product Development Program (EPDP) to increase the quantity and quality of rattan production, and increase the sale of rattan products. Small and Medium Enterprises (SMEs) involved as many as 2 (two) SMEs in Trangsan village, namely the Three Colors Rattan UKM, and the Wayan Rotan UKM with the problem of scarcity of raw materials and purchasing methods not optimal, equipment that is not feasible to use, layout not optimal, designs that change frequently. The solutions offered are training, including training in raw material purchasing methods, tool management training, and product design training, as well as upgrading equipment. The output of community service activities is that rattan production increased by more than 10% for three-color UKM, Rattan and 29% increase in UMKM production, Wayan Rotan.